The Returns to Labor and the Cyclical Behavior of Real Wages: The Canadian Case - Canzoneri, Matthew B. (The Review of Economics and Statistics, 1978)
A number of empirical studies would seem to cast doubt upon the neo-classical view of the supply side of an economy. Estimates of Cobb-Douglas production functions and the apparent procyclical movement of real wages would seem to contradict the assumption of diminishing returns to labor and the implication of neo-classical theory that factors of production are paid the value of their marginal product.' Recently, Lucas (1970) and Sargent and Wallace (1974) have outlined a theory that could reconcile these statistical results with a basically neo-classical view of supply relationships; essentially, they suggest that these paradoxical empirical observations are the result of specification error, of aggregating labor and wages over straight-time and overtime work shifts. This paper reports an attempt to evaluate empirically both the allegations against the neo-classical view and the Lucas-SargentWallace response within the context of the Canadian economy. In the first section, evidence concerning the diminishing returns to aggregate Canadian labor and the cyclical behavior of average real Canadian wages is presented. In the second, the effect of disaggregating labor is discussed. Conclusions will be found in the last section.